(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
One of the important and urgent tasks facing the knitting industry is to improve the quality, improve and update the range of products. At the same time, it is necessary to significantly increase the output of knitwear with improved heat-shielding properties, products for recreation and tourism, while ensuring the rational use of raw materials.